Production Risk of Hybrid Maize in Sugihmanik Village, Tanggungharjo Subdistrict, Grobogan Regency (Case Study: Faisal Tani Store) - Dwi Retno Mulyanti; Faisal Rizky Atmaja (PT. Anagata Sembagi Education, 2024)
This study aims to examine the impact of production factors on hybrid corn production and to assess the level of production risk in Sugihmanik Village, Tanggungharjo District, Grobogan Regency (Case Study: Faisal Tani Store). The research adopts a quantitative approach with a sample of 69 hybrid corn farmers. The data analysis method utilized the Cobb-Douglas production function with multiple linear regression and coefficient of variation analysis. Data processing was conducted using SPSS 25. The results indicated that capital, land area, and labor factors collectively influence hybrid corn production. In addition, the land area and labor variables were found to have a significant effect on hybrid corn production, while the capital variable did not show a significant effect. The coefficient of variation (CV) for production risk in hybrid corn farming in Sugihmanik Village, Tanggungharjo District, Grobogan Regency (Case Study: Faisal Tani Store) was 0.33, indicating a low level of production risk.